1988
DOI: 10.1007/bf03189927
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoking on drug metabolism in the liver and placenta: the use of cotinine in verifying smoking status

Abstract: Placental and hepatic xenobiotic-metabolising activities were studied in smokers and non-smokers, who were classified by anamnestic interview, plasma thiocyanate and plasma cotinine determinations. Plasma thiocyanate assay is inadequate in the classification of smokers and non-smokers. Plasma cotinine levels reflect more accurately the smoking status. The anamnestic smokers remained smokers and several self-declared non-smokers proved to be smokers. On the basis of plasma cotinine determination all real smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…One smoker claimed to have stopped smoking 1 month earlier, but this claim was not substantiated by the enzymatic assay and fits with the known unreliability of self-reported status of smoking mothers. 40 Placentas were collected immediately after delivery. All placentas except one smoker's placenta were obtained from vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One smoker claimed to have stopped smoking 1 month earlier, but this claim was not substantiated by the enzymatic assay and fits with the known unreliability of self-reported status of smoking mothers. 40 Placentas were collected immediately after delivery. All placentas except one smoker's placenta were obtained from vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the cotinine levels 15 and EROD activities (Table 2), all smokers had smoked at least 1 day before the delivery. One smoker claimed to have stopped smoking 1 month earlier, but this claim was not substantiated by the enzymatic assay and fits with the known unreliability of self‐reported status of smoking mothers 40 . Placentas were collected immediately after delivery.…”
Section: Methodsmentioning
confidence: 97%
“…Studies on human populations have shown a very large interindividual variability in AHH activities among individuals with comparable smoking histories [5-7,871. In one study even 1000-fold variability in AHH activity has been observed, but it must be stressed that smoking history was based on self-reports [43]. However, the inducibility of any xenobioticmetabolizing activity does not correlate with cotinine, an objective marker of smoking [44]. Another possibility is that the inducibility may be linked to the binding affinity or amount of Ah receptors [88-911.…”
Section: H Regulation Of Monooxygenase Induction In Placentamentioning
confidence: 97%
“…The dose-response curve between the number of cigarettes smoked daily and AHH activity is sigmoidal [43]. However, AHH induction does not correlate with serum cotinine levels [44]. In human liver there is very little or no induction of AHH activity in vivo, and in lungs induction is not easy to demonstrate [45], partly because of the retention and slow clearance of cigarette tar from the lungs [46].…”
Section: B Aryl Hydrocarbon Hydroxylase Activity and The Metabolism mentioning
confidence: 99%
“…The principal goal of the long‐term project was to characterize various factors and conditions which cause variability in drug metabolism in human beings. These factors included alcohol drinking and its consequences in the liver function, fibrosis and cirrhosis , and their effects on hepatic drug metabolism, cigarette smoking , other environmental exposures , diabetes and age . Already quite early during these studies, we recognized a crucial problem hampering the extrapolation of the results obtained: antipyrine and spectrally measurable cytochrome P450 are rather unspecific, even if robust, measures for drug metabolism.…”
Section: Drug‐metabolizing Enzymes In Human Liver In Vitro and In Vivomentioning
confidence: 99%